2022
DOI: 10.3389/fimmu.2022.913555
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of chromatin data supports a role for CD14+ monocytes/macrophages in mediating genetic risk for juvenile idiopathic arthritis

Abstract: IntroductionGenome wide association studies (GWAS) have identified multiple regions that confer genetic risk for the polyarticular/oligoarticular forms of juvenile idiopathic arthritis (JIA). However, genome-wide scans do not identify the cells impacted by genetic polymorphisms on the risk haplotypes or the genes impacted by those variants. We have shown that genetic variants driving JIA risk are likely to affect both innate and adaptive immune functions. We provide additional evidence that JIA risk variants i… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
3

Relationship

1
6

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 46 publications
0
4
0
Order By: Relevance
“…[ 43 ] By analyzing protein-coding regions of the genome in JIA patients compared to controls, rare genetic variants affecting immune cell function and inflammatory molecule production have been identified. [ 44 , 45 ] Additionally, copy number variations and structural variations have been detected in JIA patients, which are not captured by GWAS and EHR studies. PheWAS studies have investigated genetic associations with specific JIA subtypes and phenotypic characteristics such as joint involvement and the presence of specific autoantibodies.…”
Section: Resultsmentioning
confidence: 99%
“…[ 43 ] By analyzing protein-coding regions of the genome in JIA patients compared to controls, rare genetic variants affecting immune cell function and inflammatory molecule production have been identified. [ 44 , 45 ] Additionally, copy number variations and structural variations have been detected in JIA patients, which are not captured by GWAS and EHR studies. PheWAS studies have investigated genetic associations with specific JIA subtypes and phenotypic characteristics such as joint involvement and the presence of specific autoantibodies.…”
Section: Resultsmentioning
confidence: 99%
“…CD4+ T cells are the most frequently implicated cell type in JIA pathophysiology, but the roles of additional immune cell types such as macrophages have also been investigated. 46 To capture a wide array of immune cell types, we utilized the Database of Immune Cell Expression (DICE) to assess expression data for 15 immune cell types and states in genes that lie within genome-wide significant regions. The 2-Mb segment at 12q23.2-q23.3 shared by three distantly related subjects contains the gene DRAM1 , which encodes an autophagy induction protein that is primarily expressed by monocytes.…”
Section: Resultsmentioning
confidence: 99%
“…A role of IL-6 in oJIA has been implied decades ago ( 50 ). In addition, a recent study investigating chromatin data in monocytes in JIA patients found that IL-6 binding was one of the top enriched processes ( 21 ). Interestingly, our data showed that the magnitude of IL-6/JAK/STAT activation in monocytes was reflected in the levels of several circulating cytokines.…”
Section: Discussionmentioning
confidence: 99%